MORPHO-PHYSIOLOGICAL & HISTOLOGICAL EXAMINATION OF ORGANICALLY AND NON-ORGANICALLY CULTIVATED ANTI-DIABETIC MEDICINAL PLANTS - Tauqeer, Mohammad (Innovare Journal of Agricultural Sciences, 2016)
Objective: The present research work was designed to compare the morpho-physiological and histological characters of Trigonella foenum graecum and Ocimum sanctum cultivated by organic and non-organic farming. Methods: The open deforested area of the Department of Pharmaceutical Sciences, Rashtrasant Tukadoji Maharaj Nagpur University, Nagpur, was selected for the cultivation. For the organic cultivation, biodynamic manure and organic pesticides (neem seeds extract & fermented garlic extract) were utilized while in case of non-organic cultivation the conventional manures (urea, super phosphate & potash) and chemical pesticides (Monocrotophos & Zineb) were utilized. Different morpho-physiological (growth) traits were studied at the pre and post harvest conditions. Selected parts of the plants were also compared for the histological characters. Results: Â Both the research plants with organic treatment comparative to non-organic crop showed three days early initiation of flowers/inflorescence followed by early legumes (OTF) and fruiting (OOS). OTF found with higher mean values of height, secondary branches, flowers, secondary roots, leaves and root nodules while NTF showed the higher mean values of weight of plants and ultimately higher overall yield. Similarly OOS showed the greater mean values of all the traits (height, secondary branches, roots length and secondary roots), except the weight of whole plant that was found with the greater mean value of 279.61 g / plant in NOS. The microscopical examination revealed similar type of cellular arrangements in both the crops. Conclusion: The conclusive evidence proved the betterment of organic crop in terms of their growth and sustainability.